The Effectiveness Of The Implementation Of The 2020 Simultaneous Elections In The Time Of The Covid-19 Emergency Pandemic In Kab.Wonosobo - Prihatiningsih, Hany (International Journal of Educational Research & Social Sciences, 2022)
The effectiveness of the 2020 Simultaneous Local Elections in the midst of the COVID-19 pandemic has both positive and negative impacts. The positive impacts include the implementation of the mandate of the applicable regulations, the fulfillment of the constitutional rights of the Pilkada participants and the community, reducing the practice of local government leadership which is led by too many temporary officials, and preventing budget swelling. While the negative impacts include the higher risk of COVID-19 transmission, the potential for fraudulent practices that are increasingly vulnerable, the refusal of the Regional Head Elections has the potential to increase the number of abstentions. Efforts so that the 2020 simultaneous regional elections can be carried out properly include increasing the supervision of health protocols, maintaining integrity in the implementation of regional elections, there must be a commitment for both Pilkada participants and implementers, community discipline, there are 55 countries postponing national or local elections and national referendums. However, there are 21 countries that have not postponed elections, 9 of which have been held in the midst of the COVID-19 pandemic. South Korea became one of the countries that successfully held elections on April 15, 2020 (International Institute for Democracy and Electoral Assistance, 2020). In Indonesia, the scheduling of the simultaneous regional elections to be held in December 2020 is considered unrealistic. Due to the fact, until December 2020, the number of positive cases of COVID-19 continued to increase nationally. Many people are worried that if the local elections are held in December 2020, it will become a new cluster for the spread of COVID-19. there are 21 countries that have not postponed elections, 9 of which have been held in the midst of the COVID-19 pandemic. South Korea became one of the countries that successfully held elections on April 15, 2020 (International Institute for Democracy and Electoral Assistance, 2020). In Indonesia, the scheduling of the simultaneous regional elections to be held in December 2020 is considered unrealistic. Due to the fact, until December 2020, the number of positive cases of COVID-19 continued to increase nationally. Many people are worried that if the regional elections are held in December 2020, it will become a new cluster for the spread of COVID-19. there are 21 countries that have not postponed elections, 9 of which have been held in the midst of the COVID-19 pandemic. South Korea became one of the countries that successfully held elections on April 15, 2020 (International Institute for Democracy and Electoral Assistance, 2020). In Indonesia, the scheduling of the simultaneous regional elections to be held in December 2020 is considered unrealistic. Due to the fact, until December 2020, the number of positive cases of COVID-19 continued to increase nationally. Many people are worried that if the regional elections are held in December 2020, it will become a new cluster for the spread of COVID-19.